Control of Leaf Spot Disease on Seeds of Red Jabon (Anthocephlus macrophyllus) - Indhasari, Fitri; Azisah, Nur (Pangale Journal of Forestry and Environment, 2021)
The aims of the research were to acknowledge (1) control measures against leaf spot disease on red jabon seedlings and (2) the effect of various treatments on jabon seedlings affected by spotting. Observational data were analyzed based on Completely Randomized Design (CRD) and Variety Prints which were obtained directly from the research location through observation and measurement. Observation parameters were the number of leaves counted for all the leaves contained in Jabon seeds, plant height was measured from the base to the tip of the leaf, and the number of spot-free leaves. The results of the research indicated that (1) the treatment of Jabon seedlings had an effect on the number of leaves, plant height and number of spot-free leaves produced at the research stage of Jabon seeds and (2) treatment with NPK fertilizer gave the best effect on Jabon seedling growth. NPK fertilizer treatment gave a very significant effect on all observation parameters.